Substituent effects on the luminescent properties of europium B-diketonate complexes with dipyridophenazine ligands: a density functional theory study - Jensen, Christian (2017)
A great deal of attention is devoted to creating and characterizing new and novel luminescent lanthanide complexes due to their impressive luminescent characteristics. Unique properties include line like emission bands, long luminescent life times, and large Stokes shifts, making lanthanides ideal for applications such as organic light emitting diodes, sensor technology, biomedical assays, biomedical imaging, and LASER technology. Lanthanides by themselves, though, suffer from low molar absorptivities as a result of quantum mechanically forbidden electric dipole transitions. To overcome these limitations, ‘antenna’ ligands are coordinated to the Ln(III) ion in order to sensitize lanthanide absorption by a series of energy transfer processes. Factors essential in controlling the efficiency of ligand sensitization are the lig- and based singlet S1 and triplet T1 state energies. By controlling the substituents of the neutral donor ligand, we can effectively tune these energy levels. This study uses density functional theory (DFT) and time-dependent density functional theory (TD-DFT) to inves- tigate the electronic properties of a series of Eu(TTA)DPPZ-R (R = H, NH2, Br, CO2H, CO2CH2CH3, CO2CH3, OCH3, CH3, and NO2) complexes where TTA = thenoyltrifluo- roacetone, DPPZ = dipryrido[3,2-a:2',3'-c] phenazine. DFT-optimized molecular structures agree within the experimental values. The results of the computational study reveal that the electron withdrawing substituent groups decrease the intersystem crossing ?EI S C and energy transfer ?EET energy gap with respect to unsubstituted DPPZ. Electron donating substituent groups will increase the ?EISC and ?EET energy gaps. Absorption spectra cal- culations show good agreement with available experimental absorption data. Luminescent quantum yield measurements of the complexes decreases with decreasing ?EISC and ?EET.